Effect of Expectation of Care on Adherence to Antihypertensive Medications Among Hypertensive Blacks: Analysis of the Counseling African Americans to Control Hypertension (CAATCH) Trial. Issue 7 (23rd November 2015) - Grant, Andrea Barnes; Seixas, Azizi; Frederickson, Keville; Butler, Mark; Tobin, Jonathan N.; Jean‐Louis, Girardin; Ogedegbe, Gbenga
Abstract : Novel ideas are needed to increase adherence to antihypertensive medication. The current study used data from the Counseling African Americans to Control Hypertension (CAATCH) study, a sample of 442 hypertensive African Americans, to investigate the mediating effects of expectation of hypertension care, social support, hypertension knowledge, and medication adherence, adjusting for age, sex, number of medications, diabetes, education, income, employment, insurance status, and intervention. Sixty‐six percent of patients had an income of $20, 000 or less and 56% had a high school education or less, with a mean age of 57 years. Greater expectation of care was associated with greater medication adherence ( P =.007), and greater social support was also associated with greater medication adherence ( P =.046). Analysis also showed that expectation of care mediated the relationship between hypertension knowledge and medication adherence ( P <.05). Expectation of care and social support are important factors for developing interventions to increase medication adherence among blacks.